Dampak Alih Fungsi Lahan Pertanian terhadap Keberlanjutan Ekosistem dan Lingkungan di Kelurahan Linggajaya Kota Tasikamalaya - Nurdiani, Pani; Haryani, Sri; Tulloh, Syarip Hidayat (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2025)
The conversion of agricultural land into industrial and residential areas in Linggajaya Village, Mangkubumi District, Tasikmalaya City, has resulted in various significant ecological and environmental impacts. This study aims to analyze the impact of land conversion on ecosystem sustainability, including changes in land use, environmental degradation, and the loss of ecological functions of agricultural land. The method used was a descriptive qualitative approach, with data collection techniques through field observations, interviews, and documentation studies. The results indicate that land conversion causes land degradation, increased flooding potential, decreased biodiversity, and imbalances in the local ecosystem. These findings indicate the need for sustainable spatial planning policies and strict monitoring of agricultural land conversion to maintain environmental balance and community quality of life.